2002
DOI: 10.2355/isijinternational.42.352
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fluorine on Silicate Network for CaO-CaF2-SiO2 and CaO-CaF2-SiO2-FeOx Glasses.

Abstract: The chemical state of fluorine and the effect of fluorine addition on the degree of polymerization of silicate network have been investigated for the CaO-SiO 2 -CaF 2 and CaO-SiO 2 -CaF 2 -FeO x glasses using the Xray photoelectron spectroscopy (XPS) and Mössbauer spectroscopy measurements. The F1s XPS spectra indicate that the fluorine is dominantly coordinated with calcium rather than silicon. The O1s XPS spectra for the CaO-SiO 2 -CaF 2 glasses and the values of Fe 2ϩ /Fe 3ϩ obtained by Mössbauer spectra fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
60
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 15 publications
8
60
0
2
Order By: Relevance
“…Si-F-Ca(n) and Si-F-Na(n) species, the signals of which would be expected in the range between -123 and -152 ppm (Table 2). 25 This is in agreement with the findings by Hayashi et al who investigated the effect of fluorine addition on the network connectivity of glasses in the system SiO 2 -CaO-CaF 2 using X-ray photoelectron spectroscopy (XPS) 18 . According to their results fluorine does not affect the network connectivity or the concentration of NBO, but is coordinated with Ca…”
Section: Structural Role Of Fluoride and Sodium Ionssupporting
confidence: 81%
“…Si-F-Ca(n) and Si-F-Na(n) species, the signals of which would be expected in the range between -123 and -152 ppm (Table 2). 25 This is in agreement with the findings by Hayashi et al who investigated the effect of fluorine addition on the network connectivity of glasses in the system SiO 2 -CaO-CaF 2 using X-ray photoelectron spectroscopy (XPS) 18 . According to their results fluorine does not affect the network connectivity or the concentration of NBO, but is coordinated with Ca…”
Section: Structural Role Of Fluoride and Sodium Ionssupporting
confidence: 81%
“…From a thermodynamic viewpoint, however, research on activities that support the composition dependency of the influence of CaF 2 on the structure of the SiO 2 -CaO-CaF 2 system, as discussed in this work, have been reported by Nagata and Hayashi et al 34) They studied the activities of CaF 2 at several regions, where two solid compounds and a liquid phase coexist, and found that the activity of CaF 2 was low in the composition area with low CaF 2 and high SiO 2 content, while at lower SiO 2 content the activity of CaF 2 was high. The activity of CaF 2 was based on the models of Bills and Sasaki et al and it describes structural changes corresponding to iso-viscosity curves.…”
Section: Iso-viscosity Curves In a Molten Sio 2 -Cao-caf 2 Ternary Symentioning
confidence: 98%
“…The NBO/T ratios of powders A, B, C and D can be calculated to be 0.92, 1.48, 1.65 and 2.11, respectively, in the manner proposed by Mills 22) by assuming that fluorine predominantly bonds to calcium rather than other cations 23) and that CaF 2 does not contribute to the breakage of the silicate network. 24) Consequently, it is found that the NBO/T ratio of powder A is the smallest and the thermal diffusivity of the same is the largest among four powders. This result is in agreement with the aforementioned relationship proposed by Mills.…”
mentioning
confidence: 99%